2018
DOI: 10.29152/koiks.2018.49.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Exclusionary Labor and Partially Inclusionary Marriage Immigration Incorporation: The Cases of Japan and Korea

Abstract: Globalization has brought about significant human mobility, along with developments in IT and transportation since the early 1990s, the case of East Asia is no exception. While a huge number of workers in developing countries have been migrating to work abroad, a growing number of women have been migrating, specifically seeking to marry men in East Asia. This paper aims to elucidate which migration theories illustrate labor and/or marriage migration and incorporation in East Asia, particularly in the cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The average hourly energy consumptions of the two participants were measured at 86.61 and 140.83 kcal, respectively. Comparing with previous studies [ 14 , 15 ], this consumption amount was 5.6 times the office worker’s energy consumption and 2.6 times a car manufacturer’s energy consumption ( Table S2 ). A formwork carpenter had the most similar energy consumption to that of IWCs in this study.…”
Section: Resultsmentioning
confidence: 45%
See 1 more Smart Citation
“…The average hourly energy consumptions of the two participants were measured at 86.61 and 140.83 kcal, respectively. Comparing with previous studies [ 14 , 15 ], this consumption amount was 5.6 times the office worker’s energy consumption and 2.6 times a car manufacturer’s energy consumption ( Table S2 ). A formwork carpenter had the most similar energy consumption to that of IWCs in this study.…”
Section: Resultsmentioning
confidence: 45%
“…Actigraph is a device that recognizes human body movements on three axes and measures and records this physical activity by time zone. Although there is no standardized reference for energy consumption per hour, the results of similar studies were used as a reference [ 14 , 15 ]. One study reported the hourly energy consumption of office workers, car manufacturers, and formwork carpenters; these results were compared with the energy consumption results of participants in this study.…”
Section: Methodsmentioning
confidence: 99%